The Color of the Third Degree : Racism, Police Torture, and Civil Rights in the American South, 1930-1955 - Niedermeier, Silvan (Book collections on Project MUSE., 2019)
"Available for the first time in English, 'The Color of the Third Degree' uncovers the still-hidden history of police torture in the Jim Crow South. Based on a wide array of previously neglected archival sources, Silvan Niedermeier argues that as public lynching decreased, less visible practices of racial subjugation and repression became central to southern white supremacy. In an effort to deter unruly white mobs, as well as oppress black communities, white southern law officers violently extorted confessions and testimony from black suspects and defendants in jail cells and police stations to secure speedy convictions. In response, black citizens and the NAACP fought to expose these brutal practices through individual action, local organizing, and litigation. In spite of these efforts, police torture remained a widespread, powerful form of racial control and suppression well into the late twentieth century"--